Volume 3: 26th Computers and Information in Engineering Conference 2006
DOI: 10.1115/detc2006-99267
|View full text |Cite
|
Sign up to set email alerts
|

Towards Development of a Non-Touch Man-Machine Interface for Intelligent Presenter-Audience Collaborative Environment

Abstract: A novel, non-touch, screen pointing interface is proposed for the use of intelligent presenter/audience collaborative environment. The underlying methodology for detecting a virtual passive pointer is described. The passive pointer or device does not have any active energy source within it (as opposed to a laser pointer) and thus cannot easily be detected or identified. The modeling and simulation task is carried out by generating high resolution color images of a pointer viewing via two digital cameras with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, in particular rock fracture experiments have demonstrated that it is possible to follow the development [32,33]. In the upper figure are probability distributions: for energy P (E) ∼ E −β and for the waiting time P (τ ) ∼ τ −α .…”
Section: Criticality In Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…However, in particular rock fracture experiments have demonstrated that it is possible to follow the development [32,33]. In the upper figure are probability distributions: for energy P (E) ∼ E −β and for the waiting time P (τ ) ∼ τ −α .…”
Section: Criticality In Fracturementioning
confidence: 99%
“…Figure 5. Unpublished creep data for paper[32,33]. In the upper figure are probability distributions: for energy P (E) ∼ E −β and for the waiting time P (τ ) ∼ τ −α .…”
mentioning
confidence: 99%